The Role of Notaries in Implementing the Provisions of the Compilation of Islamic Law (KHI) on the Distribution of Inheritance to Orphans, Victims of Natural Disasters Who are in Trusteeship - Ar Rahiim Innash; Umar Ma'ruf; Arief Cholil (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
This study aims to determine and analyze the implementation of the provisions of the Islamic Law Compilation regarding the distribution of inheritance to orphans who are victims of natural disasters who are in guardianship. To find out and analyze the role of the notary in the implementation of the distribution of inheritance to orphans victims of natural disasters who are in guardianship. And to find out and analyze the obstacles and solutions to the distribution of inheritance experienced by orphans who are victims of natural disasters who are in guardianship. The research method used in this research is juridical empirical, while the data collection method uses library research and field research. The data analysis method was carried outqualitative then presented descriptively. This research resulted in the main notary's responsibility in making inheritance deeds for the share of orphans who are victims of natural disasters who are in guardianship, still following the perspective provisions of Article 106 of Act No. 23 of 2006 as amended by Act No. 24 of 2013 concerning Population Administration. , because population classification has no longer been applied since the enactment of the Population Administration Law. Notaries have the authority to make a Certificate of Inheritance regardless of population classification. The authority of the Notary in making the Certificate of Inheritance for Indonesian Citizens is based on the provisions of Article 15 of the UUJN, so that the Certificate of Inheritance for Indonesian Citizens is made in the form of this authentic deed based on the provisions of Article 1868 of the Civil Code. The role of the notary in making SKW is only to confirm that the existence of an SKW is very authentic evidence. In addition, the role of the notary in the distribution of Islamic inheritance, but the one who has full authority to determine legal recognition and termination is the Religious Court. Notary in the distribution of inheritance plays a role in making the Deed of Inheritance Statement and Certificate of Inheritance Rights. If there is a dispute, the notary can make peace deeds and/or an agreement to relinquish the rights of claim. The notary in the distribution of inheritance plays a role in making the Deed of Inheritance and Certificate of Inheritance If there is a dispute, the notary can make peace deeds and/or an agreement to relinquish the rights of claim. The notary in the distribution of inheritance plays a role in making the Deed of Inheritance and Certificate of Inheritance If there is a dispute, the notary can make peace deeds and/or an agreement to relinquish the rights of claim.